Work Below Water: The role of scuba industry in realising sustainable development goals in small island developing states. (February 2022) - Nisa, Zahidah Afrin; Schofield, Clive; Neat, Francis C.
Abstract: The scuba diving industry is vital to economies of Small Island Developing States (SIDS), providing a pivotal opportunity to realise their blue economy aspirations. This industry is fundamentally dependent on both the health of the marine environment coupled with a skilled and safe underwater labour force. This article explores the interlinkages between the United Nations Sustainable Development Goals 8 (Decent Work) and 14 (Life Below Water) in particular through the lens of workers below water and contends that the scuba diving industry can be a crucial enabler for SIDS blue economy. The SDG target 14.7, explicitly developed for SIDS, provides a direct linkage in this context. Mapping functional interlinkages between decent work and ocean sustainability policy through the lens of the diving sector offers opportunities to enhance the development of scuba industry-based skills training while simultaneously addressing the healthy ocean aspirations of SDG 14. Highlights: Small island developing states require a national strategy for their diving industry labour force. Interlinking sustainable development goals 8 and 14 enhances the national skills strategic processes. A simple conceptual policy framework establishes functional integration for this development. Island leaders need to innovate oceans goal alongside decent work creation for their blue economy. Coalition of islands dive professionals play a lead role in structuring the skills strategies.